Glassy carbon electrode modified by molecularly imprinted composite material as well as preparation method and application of glassy carbon electrode
By modifying the copper-metal organic frame/zirconia-based carbon nanocomposite on the glass carbon electrode and preparing a molecular imprinted film in combination with density functional theory screening functional monomers, the complexity and interference problems of chloramphenicol detection in food were solved, and the detection effect of high selectivity and high sensitivity was achieved.
Patent Information
- Application Number
- CN202411946670.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The prior art is difficult to achieve rapid and highly selective detection of chloramphenicol residues in foods, especially in complex food samples, where there are interfering substances, affecting the stability and sensitivity of the detection.
By modifying the copper-metal organic frame/zirconia-based carbon nanocomposite (Cu-TCPP/ZrO2@C) on the glass carbon electrode, and using density functional theory to study the interaction between chloramphenicol and functional monomer, resorcinol was screened out as functional monomer, and molecular imprinted film was prepared to form a Cu-TCPP/ZrO2@C/MIP modified electrode.
It realizes high sensitivity and selective detection of chloramphenicol, reduces the detection limit, and improves the stability and linear range of detection, which is suitable for the detection of trace chloramphenicol in animal-derived foods.
Smart Images

Figure CN119738459A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electroanalytical chemistry, and in particular relates to a glassy carbon electrode modified by a molecular imprinting composite material and a preparation method and application thereof. Background Art
[0002] Chloramphenicol is a broad-spectrum antibiotic. It is widely used in animal husbandry because it can treat respiratory and digestive system infections caused by influenza bacteria, Escherichia coli and Salmonella in animal husbandry. Recently, many studies have found that long-term consumption of food containing excessive chloramphenicol residues may accumulate in the human body and may also have a serious inhibitory effect on bone marrow hematopoiesis. It is now banned in clinical and animal husbandry industries. At present, many countries have clear restrictions on chloramphenicol residues in animal-derived foods. However, the abuse of chloramphenicol still exists, and the problem of veterinary drug residues is becoming increasingly serious. Therefore, it is of great significance to develop a rapid and highly selective method for detecting chloramphenicol in food.
[0003] The detection of chloramphenicol in food samples requires highly complex and time-consuming procedures that rely on expensive equipment, such as high-performance liquid chromatography and liquid chromatography-mass spectrometry. Therefore, there is an urgent need to develop an alternative method for rapid and sensitive analysis. Compared with the above traditional detection methods, electrochemical analysis has the advantages of simple equipment, fast response, low cost, good stability, strong selectivity, and high sensitivity. It has become the focus of current research and has been widely used in the field of antibiotic detection.
[0004] However, food samples are complex and diverse, and there may be interfering substances with similar structures, which will greatly interfere with the determination of chloramphenicol. In order to improve the selectivity of electrochemical detection methods, molecular imprinting polymers composed of cross-linked polymers have attracted widespread attention. These polymers are complementary to the template molecules in shape and size, which can accurately identify target analytes in complex systems. Therefore, the preparation of modified electrodes based on molecular imprinting polymers has become a method for constructing efficient sensing platforms. At present, how to achieve the controllable preparation of molecular imprinting composite modified electrodes, improve the stability and sensitivity of electrochemical detection, and apply them to the trace analysis of residual chloramphenicol in animal-derived foods is still a huge challenge.
[0005] Therefore, based on this, the technical solution of the present invention is proposed. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention utilizes a drop coating method to modify a copper-metal organic framework / zirconia-based carbon nanocomposite material (Cu-TCPP / ZrO2@C) on a glassy carbon electrode, uses density functional theory to establish a molecular model and calculate parameters, studies the relationship between the interaction energy (ΔE) and spatial conformation of chloramphenicol and functional monomers, determines the functional monomers used for the synthesis of molecular imprinted polymers, guides the design and preparation of molecular imprinted membranes, and then utilizes electropolymerization to polymerize the molecular imprinted membrane (MIP) on the surface of the modified electrode to obtain a molecular imprinted modified electrode.
[0007] The present invention provides a method for preparing a glassy carbon electrode modified by a molecular imprinting composite material, the preparation method comprising the following steps:
[0008] (I) Pretreatment of glassy carbon electrode:
[0009] The glassy carbon electrode is first polished with Al2O3 powder and then cleaned to obtain a pretreated glassy carbon electrode;
[0010] (II) Preparation of ZrO2@C:
[0011] (II-1) dissolving 2-aminoterephthalic acid and zirconium chloride in N,N-dimethylformamide and stirring to obtain a first mixed solution;
[0012] (II-2) adding glacial acetic acid to the first mixed solution, stirring to form a uniform solution and hydrothermally treating the solution. After the reaction is completed, filtering, washing and drying are performed in sequence to obtain UiO-66-NH2;
[0013] (II-3) calcining the UiO-66-NH2 under an inert atmosphere to obtain the ZrO2@C;
[0014] (III) Preparation of Cu-TCPP / ZrO2@C:
[0015] (III-1) N,N-dimethylformamide is mixed with ethanol, and then the ZrO2@C, Cu(NO3)·3H2O, polyvinyl pyrrolidone, and meso-tetrakis(4-carboxyphenyl)porphine are added, and the mixture is mixed to obtain a second mixed solution;
[0016] (III-2) hydrothermally treating the second mixed solution, and after the reaction is completed, washing, filtering, and drying in sequence to obtain the Cu-TCPP / ZrO2@C;
[0017] (IV) Construction of three-electrode system:
[0018] (IV-1) dropping a Cu-TCPP / ZrO2@C aqueous solution onto the surface of the pretreated glassy carbon electrode, and drying to obtain a Cu-TCPP / ZrO2@C modified glassy carbon electrode;
[0019] (IV-2) using phosphate buffer as solvent, chloramphenicol as template molecule, and resorcinol as functional monomer to obtain an electropolymerization solution;
[0020] (IV-3) placing the Cu-TCPP / ZrO2@C modified glassy carbon electrode in the electropolymerization solution, using a platinum sheet electrode as a counter electrode, Ag / AgCl as a reference electrode, and the Cu-TCPP / ZrO2@C modified glassy carbon electrode as a working electrode to build a three-electrode system;
[0021] (V) Preparation of Cu-TCPP / ZrO2@C / MIP modified electrode:
[0022] (V-1) In the three-electrode system, a molecular imprinted membrane modified electrode is obtained by cyclic voltammetry;
[0023] (V-2) Immersing the molecular imprinted membrane modified electrode in a mixed solution of methanol and acetic acid to elute the template molecules, after which the Cu-TCPP / ZrO2@C / MIP modified electrode is obtained and the preparation is completed.
[0024] Preferably, in step (I), the glassy carbon electrode is polished using 1.0 μm, 0.3 μm, and 0.05 μm Al2O3 powders in sequence.
[0025] Preferably, in step (II-2), the hydrothermal temperature is 120° C. and the hydrothermal time is 16 h;
[0026] And / or, in step (II-2), the drying temperature is 60°C.
[0027] Preferably, in step (II-3), the inert atmosphere is a nitrogen atmosphere;
[0028] And / or, in step (II-3), the calcination temperature is 600° C. and the calcination time is 3 hours.
[0029] Preferably, in step (III-2), the hydrothermal temperature is 80° C. and the heating time is 4 h;
[0030] And / or, in step (III-2), the drying temperature is 60°C.
[0031] Preferably, between step (III) and step (IV), a step of screening functional monomers is also included, which is based on the interaction at the atomic level, and uses computer numerical simulation methods to obtain information on the structure, dynamics, thermodynamics, etc. of the molecule to study the relationship between this information and function, replace some conventional experiments, reduce the number of experiments, save unnecessary material and human resources, and improve R&D efficiency to a certain extent. More specifically:
[0032] Density functional theory was used to study the interaction between chloramphenicol and functional monomers, including o-phenylenediamine, p-aminobenzoic acid, aniline, resorcinol, and pyrrole. All geometric configurations were simulated and calculated using the Gaussian 09 software package, and optimized using the B3LYP functional and the def2-svp basis set. The single-point energies of chloramphenicol, functional monomers, and chloramphenicol-functional monomer polymers were calculated at the wb97xb / def2tzvp level. By comparing the interaction energy between chloramphenicol and the functional monomers, resorcinol was selected as the functional monomer with the maximum interaction energy with chloramphenicol, and resorcinol was selected as the optimal functional monomer for the molecular imprinting system.
[0033] Furthermore, the calculation method takes into account the implicit solvent model (SMD) during the calculation process.
[0034] Preferably, in step (V-1), cyclic voltammetry is used to scan 10 times in the voltage range of -0.2 to 1.0 V at a scanning speed of 50 mV / s to obtain a molecularly imprinted membrane modified electrode.
[0035] Based on the same technical concept, the present invention also provides a glassy carbon electrode modified with a molecular imprinting composite material obtained by the above preparation method.
[0036] Based on the same technical concept, the present invention also provides an application of a glassy carbon electrode modified by the molecular imprinting composite material in detecting chloramphenicol. The glassy carbon electrode modified by the molecular imprinting composite material can improve detection sensitivity and selectivity, widen the linear range, and reduce the detection limit in the process of detecting chloramphenicol.
[0037] The beneficial effects of the present invention are:
[0038] 1. The present invention uses the Cu-TCPP / ZrO2@C composite sensitizing material with large specific surface area, high catalytic activity and high stability to prepare the modified electrode, thereby increasing the electrochemical signal and making the electrochemical analysis method have good detection sensitivity and stability.
[0039] 2. The present invention calculates the interaction energy between chloramphenicol and several functional monomers to be selected based on molecular simulation software, and screens out functional monomers using molecular dynamics simulation calculation methods, which has the advantages of good prediction effect, saving time and money.
[0040] 3. The molecular imprinted membrane prepared by the screened functional monomers of the present invention generates holes in the membrane that match the template molecules, forming a transmission channel that allows chloramphenicol to pass continuously, quickly and smoothly. Therefore, under the same conditions, the molecular imprinted membrane prepared by the method of the present invention has a stronger specific recognition ability.
[0041] 4. The present invention combines the synergistic amplification of electrochemical signals after Cu-TCPP / ZrO2@C modified electrodes with the high selectivity of molecular imprinting materials, and provides a method for preparing a molecular imprinting composite material modified glassy carbon electrode based on the synergistic effect of Cu-TCPP / ZrO2@C, and applies it to the detection of chloramphenicol in food. Compared with other methods for detecting chloramphenicol, the method provided by the present invention has simple equipment, convenient operation, good selectivity, and significant potential for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0043] Figure 1 This is the preparation flow chart of Cu-TCPP / ZrO2@C / MIP modified electrode.
[0044] Figure 2 This is the stable conformation diagram formed by chloramphenicol and resorcinol.
[0045] Figure 3 The cyclic voltammograms of various modified electrodes in a mixture of 5mmol / LK3[Fe(CN)6] and 0.1mol / LKCl. Among them: (a) bare glassy carbon electrode, (b) Cu-TCPP modified electrode, (c) ZrO2@C modified electrode, (d) Cu-TCPP / ZrO2@C modified electrode, (e) Cu-TCPP / ZrO2@C / MIP modified electrode (before elution), (f) Cu-TCPP / ZrO2@C / MIP modified electrode (after elution), (g) Cu-TCPP / ZrO2@C / MIP modified electrode (after adsorption of 10μmol / L chloramphenicol solution).
[0046] Figure 4These are the differential pulse voltammetry curves of various modified electrodes in phosphate buffer solution containing 10 μmol / L chloramphenicol: (a) bare glassy carbon electrode, (b) Cu-TCPP / ZrO2@C modified electrode, and (c) Cu-TCPP / ZrO2@C / MIP modified electrode.
[0047] Figure 5 The present invention is a differential pulse voltammetry curve of a chloramphenicol solution with a chloramphenicol concentration ranging from 0.01 to 50 μmol / L using a molecular imprinting composite material modified glassy carbon electrode for detecting chloramphenicol in an embodiment with a phosphate buffer solution as a background solution.
[0048] Figure 6 It is a linear fitting diagram of the detection signal of the molecular imprinting composite material modified glassy carbon electrode for detecting chloramphenicol in the embodiment with phosphate buffer solution as background solution and chloramphenicol concentration ranging from 0.01 to 50 μmol / L. DETAILED DESCRIPTION
[0049] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0050] Example
[0051] This embodiment provides a method for preparing a glassy carbon electrode modified with a molecular imprinting composite material. The preparation flow chart is as follows: Figure 1 As shown, and includes the following specific steps:
[0052] (I) Pretreatment of glassy carbon electrode:
[0053] The glassy carbon electrode was polished to a mirror surface on suede with 1.0 μm, 0.3 μm, and 0.05 μm Al2O3 powders in turn, and then ultrasonically cleaned with deionized water and ethanol for 1 minute respectively. After each ultrasonic cleaning, it was rinsed with deionized water to obtain a pretreated glassy carbon electrode.
[0054] (II) Preparation of ZrO2@C:
[0055] 2-Aminoterephthalic acid (H2BDC-NH2, 0.0816g) and zirconium chloride (ZrCl4, 0.105g) were dissolved in N,N-dimethylformamide (DMF, 45mL). The above solution was stirred vigorously for 30 minutes to form a uniform solution. Then 8mL of glacial acetic acid was added to the above mixed solution and stirred for 30min. The obtained suspension was transferred into a 50mL polytetrafluoroethylene autoclave and hydrothermally reacted at 120°C for 16 hours. After naturally cooling to room temperature, it was filtered, washed three times with DMF and methanol, and dried at 60°C to obtain UiO-66-NH2. The synthesized UiO-66-NH2 was heated to 600°C under a nitrogen atmosphere and calcined for 3 hours, and the product ZrO2@C was collected.
[0056] (III) Preparation of Cu-TCPP / ZrO2@C:
[0057] 0.006g ZrO2@C, 0.012g Cu(NO3)·3H2O, and polyvinylpyrrolidone (PVP, 20mg) were dissolved in 20mL DMF / ethanol mixture (volume ratio of 3:1) at room temperature. After being fully mixed, medium-tetra(4-carboxyphenyl)porphine (TCPP, 0.0395g) was added to the above solution and ultrasonicated for 30 minutes to form a uniform solution. The obtained mixed solution was transferred into a 50mL polytetrafluoroethylene autoclave and hydrothermally reacted at 80°C for 4 hours. After cooling naturally to room temperature, it was filtered, washed three times with ethanol and distilled water, and dried at 60°C to obtain Cu-TCPP / ZrO2@C.
[0058] (IV) Screening of functional monomers
[0059] Density functional theory was used to study the interaction between chloramphenicol and functional monomers, including o-phenylenediamine, p-aminobenzoic acid, aniline, resorcinol, and pyrrole. All geometric configurations were simulated and calculated using the Gaussian 09 software package, and the implicit solvent model (SMD) was considered. The B3LYP functional and def2-svp basis sets were optimized, and the single-point energies of chloramphenicol, functional monomers, and chloramphenicol-functional monomer polymers were calculated at the wb97xb / def2tzvp level. By comparing the interaction energy between chloramphenicol and the functional monomers, resorcinol was selected as the functional monomer with the maximum interaction energy with chloramphenicol, and its stable conformation is as follows: Figure 2 Therefore, resorcinol was selected as the best functional monomer for the molecular imprinting system.
[0060] (V) Construction of three-electrode system:
[0061] Use a pipette to transfer 7 μL of Cu-TCPP / ZrO2@C aqueous solution to the surface of the glassy carbon electrode and dry it at room temperature to obtain a Cu-TCPP / ZrO2@C modified glassy carbon electrode. Use phosphate buffer as solvent, chloramphenicol as template molecule, and resorcinol as functional monomer to obtain an electropolymerization solution. Place the Cu-TCPP / ZrO2@C modified glassy carbon electrode in the above electropolymerization solution, use a platinum electrode as the counter electrode, Ag / AgCl as the reference electrode, and the Cu-TCPP / ZrO2@C modified glassy carbon electrode as the working electrode to build a three-electrode system.
[0062] (VI) Preparation of Cu-TCPP / ZrO2@C / MIP modified electrode:
[0063] Cyclic voltammetry was used to scan 10 cycles at a scanning speed of 50 mV / s in the voltage range of -0.2 to 1.0 V to obtain a molecular imprinted membrane modified electrode. After the electrode was naturally dried, it was immersed in a methanol / acetic acid mixed solution (volume ratio of 9:1) for 20 minutes to elute the template molecules, and a Cu-TCPP / ZrO2@C / MIP modified glassy carbon electrode was obtained.
[0064] Performance test case
[0065] Conventional electrochemical performance tests were performed on the modified electrodes obtained in the examples, and the results were good.
[0066] (1) Cyclic voltammetry test
[0067] The unmodified glassy carbon electrode, Cu-TCPP modified electrode, ZrO2@C modified electrode, Cu-TCPP / ZrO2@C modified electrode, Cu-TCPP / ZrO2@C / MIP modified electrode before and after elution, and Cu-TCPP / ZrO2@C / MIP modified electrode after adsorbing 10 mol / L chloramphenicol solution were used as working electrodes, a platinum electrode was used as an auxiliary electrode, and an Ag / AgCl electrode was used as a reference electrode to form a three-electrode system. The system was placed in a mixed solution of 5 mmol / L K3[Fe(CN)6] and 0.1 mol / L KCl for cyclic voltammetry scanning (scanning parameters: voltage range of -0.2 to 0.8 V, scan rate of 50 mV / s). Figure 3As shown in the figure, the Cu-TCPP / ZrO2@C / MIP modified electrode before elution is covered with an insulating molecular imprinting membrane, which hinders the electron transfer between potassium ferrocyanide and the electrode, and the current signal is very low. However, the peak current signal of potassium ferrocyanide is significantly increased in the Cu-TCPP / ZrO2@C / MIP modified electrode after elution. This is because the chloramphenicol in the imprinting membrane is eluted, leaving specific recognition holes, which become channels for electron transfer. When the eluted Cu-TCPP / ZrO2@C / MIP modified electrode is immersed in a solution containing chloramphenicol, some specific recognition holes are occupied by chloramphenicol molecules, and electron transfer is hindered again. At this time, the peak current value becomes smaller again.
[0068] (2) Differential pulse voltammetry test
[0069] A three-electrode system was formed with an unmodified glassy carbon electrode, a Cu-TCPP / ZrO2@C modified electrode and a Cu-TCPP / ZrO2@C / MIP modified electrode as working electrodes, a platinum electrode as an auxiliary electrode and an Ag / AgCl electrode as a reference electrode. The system was placed in a phosphate buffer solution containing 10 μmol / L chloramphenicol for differential pulse voltammetry scanning (scanning parameters: scanning potential range of -0.4 to 0.4 V, scanning rate of 50 mV / s). The test results are shown in Figure 2. Figure 4 As shown. The Cu-TCPP / ZrO2@C / MIP modified electrode has the strongest response current to chloramphenicol. This is because the Cu-TCPP / ZrO2@C composite material has excellent conductivity, high specific surface area and abundant active sites, which provides the best place for binding chloramphenicol. MIP has an imprinted cavity that is complementary to the structure of chloramphenicol and exhibits good recognition ability for chloramphenicol, so that chloramphenicol molecules can be quickly adsorbed on the electrode surface. The synergistic effect between MIP and Cu-TCPP / ZrO2@C greatly improves the sensing performance of the electrode. Therefore, the Cu-TCPP / ZrO2@C / MIP modified electrode can obtain satisfactory results.
[0070] A chloramphenicol solution of a certain concentration was prepared with a phosphate buffer solution of pH=6.5 as solvent, and the concentration range of the chloramphenicol solution was 0.01-50 μmol / L. A three-electrode system was formed with a Cu-TCPP / ZrO2@C / MIP modified electrode as the working electrode, a platinum electrode as the auxiliary electrode, and an Ag / AgCl electrode as the reference electrode. The system was placed in a chloramphenicol solution in the above concentration range for differential pulse voltammetry scanning (scanning parameters: scanning potential range of -0.4-0.4V, scanning rate of 50mV / s). The differential pulse voltammetry curve of the above chloramphenicol solution is shown in FIG. Figure 5 The peak current of the differential pulse voltammetry curve shows regularity and a good linear relationship (as shown in Figure 2). Figure 6As shown): I1 = 0.8136C + 1.1633, R 2 =0.9956(0.01~5μmol / L), I2=0.44861C+2.9165, R 2 =0.9988 (5-50 μmol / L). The lower limit of detection is 0.005 μmol / L (S / N=3, which means that the detection limit is calculated under the condition of signal-to-noise ratio of 3). It can be seen that the Cu-TCPP / ZrO2@C / MIP modified electrode in Example 1 has a wide detection linear range, a low detection limit, and good detection performance for chloramphenicol.
[0071] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a glassy carbon electrode modified with a molecular imprinting composite material, characterized in that: The preparation method comprises the following steps: (I) Pretreatment of glassy carbon electrode: The glassy carbon electrode is first polished with Al2O3 powder and then cleaned to obtain a pretreated glassy carbon electrode; (II) Preparation of ZrO2@C: (II-1) dissolving 2-aminoterephthalic acid and zirconium chloride in N,N-dimethylformamide, and stirring to obtain a first mixed solution; (II-2) adding glacial acetic acid to the first mixed solution, stirring to form a uniform solution and hydrothermally treating the solution, and after the reaction is completed, filtering, washing and drying are performed in sequence to obtain UiO-66-NH2; (II-3) calcining the UiO-66-NH2 under an inert atmosphere to obtain the ZrO2@C; (III) Preparation of Cu-TCPP / ZrO2@C: (III-1) N,N-dimethylformamide is mixed with ethanol, and then the ZrO2@C, Cu(NO3)·3H2O, polyvinyl pyrrolidone, and meso-tetrakis(4-carboxyphenyl)porphine are added, and the mixture is mixed to obtain a second mixed solution; (III-2) hydrothermally treating the second mixed solution, and washing, filtering and drying in sequence after the reaction to obtain the Cu-TCPP / ZrO2@C; (IV) Construction of three-electrode system: (IV-1) dropping a Cu-TCPP / ZrO2@C aqueous solution onto the surface of the pretreated glassy carbon electrode, and drying to obtain a Cu-TCPP / ZrO2@C modified glassy carbon electrode; (IV-2) using phosphate buffer as solvent, chloramphenicol as template molecule, and resorcinol as functional monomer to obtain an electropolymerization solution; (IV-3) placing the Cu-TCPP / ZrO2@C modified glassy carbon electrode in the electropolymerization solution, using a platinum sheet electrode as a counter electrode, Ag / AgCl as a reference electrode, and the Cu-TCPP / ZrO2@C modified glassy carbon electrode as a working electrode to build a three-electrode system; (V) Preparation of Cu-TCPP / ZrO2@C / MIP modified electrode: (V-1) In the three-electrode system, a molecular imprinted membrane modified electrode is obtained by cyclic voltammetry; (V-2) Immersing the molecular imprinted membrane modified electrode in a mixed solution of methanol and acetic acid to elute the template molecules, after which the Cu-TCPP / ZrO2@C / MIP modified electrode is obtained and the preparation is completed.
2. The method for preparing a glassy carbon electrode modified with a molecularly imprinted composite material according to claim 1, characterized in that: In step (I), the glassy carbon electrode is polished using 1.0 μm, 0.3 μm, and 0.05 μm Al2O3 powders in sequence.
3. The method for preparing a glassy carbon electrode modified with a molecularly imprinted composite material according to claim 1, characterized in that: In step (II-2), the hydrothermal temperature is 120° C. and the hydrothermal time is 16 h; And / or, in step (II-2), the drying temperature is 60°C.
4. The method for preparing a glassy carbon electrode modified with a molecularly imprinted composite material according to claim 1, characterized in that: In step (II-3), the inert atmosphere is a nitrogen atmosphere; And / or, in step (II-3), the calcination temperature is 600° C. and the calcination time is 3 hours.
5. The method for preparing a glassy carbon electrode modified with a molecularly imprinted composite material according to claim 1, characterized in that: In step (III-2), the hydrothermal temperature is 80°C and the hydrothermal time is 4 hours; And / or, in step (III-2), the drying temperature is 60°C.
6. The method for preparing a glassy carbon electrode modified with a molecularly imprinted composite material according to claim 1, characterized in that: Between step (III) and step (IV), a step of screening functional monomers is also included; The method for screening the functional monomer is: using density functional theory to compare the interaction between chloramphenicol and the functional monomer, and screening out resorcinol as the functional monomer with the maximum interaction energy with chloramphenicol, and using resorcinol as the best functional monomer of the molecular imprinting system.
7. The method for preparing a glassy carbon electrode modified with a molecularly imprinted composite material according to claim 1, characterized in that: In step (V-1), cyclic voltammetry is used to scan 10 times in the voltage range of -0.2 to 1.0 V at a scanning speed of 50 mV / s to obtain a molecularly imprinted membrane modified electrode.
8. A glassy carbon electrode modified with a molecular imprinting composite material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the glassy carbon electrode modified with the molecular imprinting composite material according to claim 8 in detecting chloramphenicol.
Citation Information
Patent Citations
Ppy-MIP / ZrO2atC / NPG / GCE molecularly imprinted electrochemical sensor as well as preparation method and application thereof
CN114755278A
Method for detecting baicalin and diclofenac sodium by electrochemical sensor based on Cu-TCPP / BN composite material
CN116106381A
Efficient carrier separation photocatalyst based on metal organic framework material and preparation method
CN117861730A
Electrochemical sensor and preparation method therefor and use thereof in detecting ginsenoside rg3
WO2023015824A1